MENINGKATKAN PERAN GENERASI MUDA DALAM MEMBANGUN PEREKONOMIAN MASYARAKAT - Bahri majid (Journal of Career Development, 2023)
The role of the younger generation in building the community's economy is very important, especially for Batara Gowa SMAS students. Our Community Service implementation focuses on the younger generation or Generation Z referring to those who were born between 1995 and 2010 and are currently still in high school grades X and XI, namely SMAS Batara Gowa students. They are a group that has grown in the midst of very rapid scientific and technological advances. The aim of implementing this PKM is that Batara Gowa SMAS students are expected to be able to contribute to community economic development, expand career opportunities, develop creativity and innovation, increase branding and marketing awareness